Adapting Online Patient Decision Aids: Effects of Modality and Narration Style on Patients' Satisfaction, Information Recall and Informed Decision Making. Issue 9 (1st September 2020) - De Looper, Melanie; Damman, Olga; Smets, Ellen; Timmermans, Danielle; Van Weert, Julia
Abstract : Audiovisual and narrative information are often used in online decision aids. However, few studies have tested whether these strategies are more effective compared to other types of information. We tested the effect of these strategies on satisfaction with the information, recall and informed decision-making in a 2 (Modality: audiovisual vs. textual) x 2 (Narration style: narrative vs. factual) experimental design. Data was collected in an online experiment among 262 analogue cancer patients. Since most cancer patients are older people, we also assessed if the effectiveness of these strategies differs depending on the patient's age. Data was analyzed using Structural Equation Modeling. Findings showed audiovisual modality had a positive effect on satisfaction. Moreover, audiovisual modality improved recall, both directly and indirectly via satisfaction, which subsequently resulted in better-informed decision-making. Narratives resulted in more satisfaction, but not better recall or informed decision-making. These effects were found in patients of all ages.